Developing Knowledge for Social Change: A Response to Critical Approaches to Science and Religion - Loumagne, Megan (Zygon, 2026)
This is a response to the 2023 volume entitled Critical Approaches to Science and Religion. It examines the role of ontic commitments in shaping ethical claims. It also considers the possibility of objectivity in knowledge projects.